Kisah Pengusiran Nabi Adam dalam Al-Qur’an: Kajian QS. Al-A’rāf (7): 19-25 Perspektif Maqāshid Al-Qur’ān Abdul Mustaqim - Maulana, M. Rizqi; Rifdi, Moh. (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Verses of the story are one of the styles of language used to reveal the content of moral values ​​contained in the Qur'an. One of the stories contained in the Qur'an is about the expulsion of the Prophet Adam from heaven because he violated Allah SWT's command not to eat the fruit of khuldi. Many previous articles have discussed the story of the Prophet Adam in the Qur'an, but those that focus on the aspect of expulsion to reveal the moral values ​​of the story are still rare. The study uses the approach of maqāshid al-Qur'ān Abdul Mustaqim to reveal the moral values ​​contained in the story of the expulsion of the Prophet Adam. Of the five fundamental values ​​of maqāshid initiated by Abdul Mustaqim, there are at least two fundamental values ​​contained in the story of the expulsion of the Prophet Adam, namely equality (al-Musāwah) and freedom and responsibility (al-Hurriyah ma'a al-Masuliyyah).